The power of the pyre – A holistic study of cremation focusing on charcoal remains. (January 2016) - O'Donnell, Lorna
Abstract: The pyre was an integral part of the ritual of cremation, yet the actual wood that fuelled pyres has rarely been investigated from Bronze Age sites. This research examines environmental results focusing on charcoal data from the largest Bronze Age cremation cemetery discovered in Ireland, Templenoe. A holistic approach combines charcoal, plant macrofossil, osteological and artefactual results to provide new insights into the cremation process in prehistory. It demonstrates that particular trees (oak, pomaceous fruitwood and ash) were selected over 600 years to fuel the cremation pyres at Templenoe, trends which are reflected regionally in both Ireland and Britain. Comparison of charcoal with osteological data suggests that the selection of wood did not reflect age or sex. Pyre material was consistently buried with the cremated bones in graves indicating the importance of the pyre itself in the overall cremation process. Empty funerary pits or possible "cenotaphs" contain the exact same wood taxa as the graves with bone, suggesting that it may be correct to interpret these as graves. It is possible that pyre material could have been buried as a proxy for the body. Highlights: New multi-proxy environmental data from an Early-Middle Bronze Age cremation cemetery in Ireland. Particular trees selected for up to 600 years to fuel cremation pyres. Pyre material was important, it may even have been buried as a proxy for the body. Charcoal is a crucial interpretative tool from archaeological sites.